López domínguez, luis horacio, (comp.) obra educativa de santander 1819 -1826. (1991)
LÓPEZ DOMÍNGUEZ, Luis Horacio, (comp.) Obra educativa de Santander 1819 -1826. Fundación Francisco de Paula Santander. Bogotá, 1990. 3v